Metodologias do ensino da geografia em estabelecimentos escolares do Brasil e da França - Uberândia/Paris (2002-2003) - Ulhôa, Leonardo Moreira (2005)
Interest in discovering the reasons for student s lack of interest/stimulus in Geography as a school subject gave rise to this study. Thus, we examined the educational methodologies used in the pedagogic practice developed in the fifth grade of the elementary school in Brazil (Uberlândia) and in "sixiéme" in schools in France (Paris). We have redeemed the interest and attraction that this subject could have in the schools by questioning the old conception that the teaching of Geography is not important, because it only demands memorization and that it does not develop the thinking and the critical spirit of the students. Our research shows signs for the improvement of the methodology used in present didactic books by means of: the images and the language of the midia; field work; the valorization of maps; and of the students daily routine as a start of the pedagogic practice, whenever possible. By using these pedagogic practices, we understand that the reconstruction of geographical knowledge and the redimensioning of the educational practices are possible. In this manner the delights of learning Geography as a school subject can be accomplished. The renewal of our daily pedagogy in the classroom becomes more and more important if we wish to impart to the students the conditions necessary to assimilate the knowledge which study of Geography provides for a greater understanding of challenges we face in today s world.